Етика и медицинска генетика - Трајковски, Владимир (Faculty of Philosophy, UKIM, Skopje, Macedonia, 1999)
Fast development of medical genetics and it’s subdisciplines is noticed in last thirty years. Modern diagnostic methods made possible to establish human genom and its impairment. In human genetics, ethic is main principle in working. Ethic is science about biggest goodness for human or society, and its aim protecting human health. Today's conditions for leaving and science development open a wide way for ethical approaches, but also for non-ethical manipulations with human even before his conception. We must keep to attitude that without law, with our behavior will must conduct our conscience. It is best to have neutral eugenetic attitude, which allows free ethical choice of each individual, in any case, for the well being of man.
Ethics and Medical Genetics
Keywords: етика, медицинска генетика, дефектологија